Neutralization of excessive CCL28 improves wound healing in diabetic mice - Chen, Zhenlong; Haus, Jacob M.; DiPietro, Luisa A.; Koh, Timothy J.; Minshall, Richard D. (Frontiers in Pharmacology, 2023)
Introduction: Chronic, non-healing skin wounds such as diabetic foot ulcers (DFUs) are common in patients with type 2 diabetes mellitus (T2DM) and often result in limb amputation and even death. However, mechanisms by which T2DM and inflammation negatively impact skin wound healing remains poorly understood. Here we investigate a mechanism by which an excessive level of chemokine CCL28, through its receptor CCR10, impairs wound healing in patients and mice with T2DM. Methods & Results: Firstly, a higher level of CCL28 was observed in skin and plasma in both patients with T2DM, and in obesity-induced type 2 diabetic db/db mice. Compared with WT mice, adipose tissue from db/db mice released 50% more CCL28, as well as 2- to 3-fold more IL-1β, IL-6, and TNF-α, and less VEGF, as determined by ELISA measurements. Secondly, overexpression of CCL28 with adenovirus (Adv-CCL28) caused elevation of proinflammatory cytokines as well as CCR10 expression and also reduced eNOS expression in the dorsal skin of WT mice as compared with control Adv. Thirdly, topical application of neutralizing anti-CCL28 Ab dose-dependently accelerated wound closure and eNOS expression, and decreased IL-6 level, with an optimal dose of 1 μg/wound. In addition, mRNA levels of eNOS and anti-inflammatory cytokine IL-4 were increased as shown by real-time RT-PCR. The interaction between eNOS and CCR10 was significantly reduced in diabetic mouse wounds following application of the optimal dose of anti-CCL28 Ab, and eNOS expression increased. Finally, enhanced VEGF production and increased subdermal vessel density as indicated by CD31 immunostaining were also observed with anti-CCL28 Ab. Discussion: Taken together, topical application of neutralizing anti-CCL28 Ab improved dorsal skin wound healing by reducing CCR10 activation and inflammation in part by preventing eNOS downregulation, increasing VEGF production, and restoring angiogenesis. These results indicate anti-CCL28 Ab has significant potential as a therapeutic strategy for treatment of chronic non-healing diabetic skin wounds such as DFUs.